Potential of Three Taro (Colocasia esculenta L.) Cultivars as Animal Feed - Hidayat Bambang Setyawan; Roni Yulianto; Oviaki Zelin; Listya Purnamasari (Universitas Gadjah Mada, 2021)
The growth and yield of taro (Colocasia esculenta L.) plants are influenced by the planting material. The use of planting material derived from corms is expected to improve the quality and quantity of taro growth and yield. This research aimed to find the best type of planting material and cultivars for taro growth and the potential of taro plants as animal feed. The experiment was carried out in Jember, East Java ( elevation ±89 m asl). The experiment used the randomized completed block design method with two treatment factors, the type of planting material (B) as the first factor (B1: taro corms, B2: taro tiller, B3: taro stolon) and the use of taro cultivars (V) as the second factor (V1: green taro, V2: ketan taro, V3: Sukabumi taro). The treatment was repeated four times. The results showed that there was an interaction between the use of taro planting material and taro cultivar that could influence the tuber weight per plant. The types of planting material had a significant effect on the number of tillers, leaf area, corm weight and diameter, and the planting of several taro cultivars significantly affected all observed variables. The treatment that gave the best results was planting material from taro tuber (B1) and Sukabumi cultivar (V3) with a tuber weight yield of 362.58 g (±14.5 tons/ha). Meanwhile, the Sukabumi cultivar (V3) had the best potential as animal feed. Overall, the stems and leaves of taro had a protein content of 1.19–2.02%, while the corms had 2.82–4.09%.